THE NEGATION OF THE PASSIVE VOICE IN THE PERFECT CONTINUOUS TENSES OF THE ENGLISH LANGUAGE AND THE CROSS-LINGUISTIC PROOF OF ITS NECESSITY BASED ON THE UZBEK ASPECTUAL SYSTEM - Rustamov Saidg‘offorxon Asilbek o‘g‘li (International Journal of Literature and Language Studies, 2026)
This article analyzes the dogma regarding the non-use of the Passive Voice in the Perfect Continuous tenses within English language textbooks. The purpose of the study is to prove the necessity of the '' formula in accurately translating the Uzbek